Training and leadership profile in adapted sport coaches and the implication in athletes with intellectual disabilities - Pires, Pedro (2020)
The coach role has been widely studied, and it has become a ruling factor in achievement of more knowledge, and by improving their competence. However, most studies are related to regular sports, making it essential to develop the same process in adapted sports. The present study aims to create a project that intends to establish a coaching profile in the field of Adapted Sport through the perspectives of coaches and athletes with Intellectual Disability (ID). Quantitative methods will be used as resource. We will question coaches through questionnaires for the mentoring profile (CPQ; SCDS; SCLS; SCPS) whereas for the leadership profile we will use the Sports Leadership Scale (ELD). As for the athletes they will be questioned through: BRSQ; BPNSS; SWLS and PANAS and Leadership Scale for Sports - LSS - Perception Version and Preferences). The results obtained in the described process, will serve to develop out the construction of a profile of training and performance for the coaches in the area of adapted sport.